Aqueous electrocatalytic N2 reduction for ambient NH3 synthesis: recent advances in catalyst development and performance improvement. Issue 4 (3rd January 2020) - Zhu, Xiaojuan; Mou, Shiyong; Peng, Qiling; Liu, Qian; Luo, Yonglan; Chen, Guang; Gao, Shuyan; Sun, Xuping
Abstract : In this review, we summarize recent advances in the design and development of electrocatalysts for the N2 reduction reaction. We also discuss the strategies to boost catalytic performances, the methods for reliable NRR experiments, and perspectives for further research directions. Abstract : Electrochemical N2 reduction has emerged as an environmentally benign alternative to the Haber–Bosch process for sustainable NH3 synthesis under ambient reaction conditions, and considerable recent attention has focused on electrocatalytic NH3 synthesis from N2 and H2 O in aqueous media. In this Minireview, we summarize the recent advances in the development of electrocatalysts for the N2 reduction reaction (NRR). Strategies to boost the NRR performances are also discussed. Perspectives for further research directions are provided finally.